Wealth and Inequality: A Qualitative Inquiry into Institutional Dysfunction in Resource-Rich Muslim Nations - Teni solihat; Abdul Karim Amrullah; Nurlailiyah Aidatus Sholihah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Several Muslim-majority countries endowed with abundant natural resources (NR) continue to face persistent development stagnation and severe social inequality, raising critical questions about the paradox of resource wealth. This study aims to qualitatively examine how institutional dysfunction influences wealth distribution and development trajectories in these contexts. Employing a qualitative approach with a case study design, the research focuses on resource-rich Muslim-majority countries, using Indonesia as a primary case due to its substantial natural resources and Muslim population exceeding 80%. Data were collected through policy document analysis and triangulated with media reports to ensure validity. Findings reveal that weak institutional capacity, entrenched corruption, and the dominance of political-economic elites are key drivers of persistent inequality and developmental inertia. These structural deficiencies prevent resource wealth from translating into broad-based prosperity, instead reinforcing elite capture and social disparity. The study contributes to the literature on resource governance by demonstrating that natural resource abundance, without robust institutional frameworks, intensifies the resource curse in Muslim-majority contexts. Practical implications underscore the urgency of institutional reform and the design of governance models tailored to socio-cultural and political realities, aiming to achieve inclusive and sustainable development. This research advances understanding of the intersection between institutional quality, resource wealth, and inequality, offering policy insights for governments and international development agencies operating in similar contexts.